2008
DOI: 10.1097/tp.0b013e318174d857
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acute and Chronic Rejection in Multiple Organ Allografts From Retransplantation and Autopsy Cases of Multivisceral Transplantation

Abstract: Our study clearly indicated variation in organ susceptibility to ACR and CR. Small intestinal allografts were the most susceptible organ to ACR in frequency and severity. Pancreatic allografts may be more susceptible to CR in comparison with ACR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Multivisceral transplantation (MVT) is one of the forms of SBT. Previous reports have suggested that the small intestinal allograft (particularly the ileum) is the most susceptible organ to acute cellular rejection (ACR) in frequency and severity when compared with other allografts within the MVT and it has been recognized as the Achilles heel and critical organ of MVT [4]. Therefore, in the management of intestinal graft, the early detection and treatment of ACR is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Multivisceral transplantation (MVT) is one of the forms of SBT. Previous reports have suggested that the small intestinal allograft (particularly the ileum) is the most susceptible organ to acute cellular rejection (ACR) in frequency and severity when compared with other allografts within the MVT and it has been recognized as the Achilles heel and critical organ of MVT [4]. Therefore, in the management of intestinal graft, the early detection and treatment of ACR is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Multivisceral transplantation (MVT) is one of the forms of SBT. Previous reports have suggested that the small intestinal allograft (particularly the ileum) is the most susceptible organ to ACR in frequency and severity when compared with other allografts within the MVT and it has been recognized as the "Achilles heel" and critical organ of MVT (4). Therefore, accurate diagnosis and treatment of ACR are critical for posttransplant patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulating peritoneal sclerosis has also been described in a few cases, although this finding is usually evident only in the operating room [38]. Most studies of chronic rejection have focused on the histology of explants after death or graft enterectomy [17,37]. This is due to the fact that intestinal mucosal biopsies are too superficial to evaluate the small and medium-sized vessels located in the muscularis mucosae layer of the intestinal wall.…”
Section: Chronic Rejectionmentioning
confidence: 95%
“…In a paper describing the relative frequency of rejection in multivisceral transplant organ explant specimens, overall detection of ACR in the small intestine was in 25.5% of cases, 12.2% in the stomach, and 16% in the large intestine. In patients undergoing ACR, the relative frequencies were 80.0% in the small intestine, 38.5% in the stomach, and 33.3% in the large intestine [17]. If the distal ileum cannot be reached, the proximal jejunum can be sampled as an alternate site.…”
Section: Diagnosismentioning
confidence: 99%